Ortaöğretimde giysi tasarımı eğitimi - Dizman, Ayşe Altundağ (My University, 2007)
Bu tez çalışmasında; Türk Milli Eğitim Sistemi, Milli Eğitim Bakanlığı’nın tarihsel gelişimi, örgüt yapısı ve görevleri, örgün ve yaygın eğitime bağlı ortaöğretimde Mesleki ve Teknik Ortaöğretim Kurumları incelendiğinde “ Giysi Tasarımı” eğitiminin Kız Teknik Öğretim Genel Müdürlüğü’ne bağlı okullarda, “Tekstil Konfeksiyon Alan” altında verildiği görülmüştür. Tekstil Konfeksiyon Alan alan altında verilen Giysi Tasarımı eğitiminin tanımı, amaçları, içeriği, ders programları, öğretim süreçleri, materyalleri (Modülleri) incelenmiştir. Tekstil Konfeksiyon bölümü olan okullar listelenerek, bu okullarda Giysi Tasarımı ( Kadın, Erkek, Çocuk ve İç Giyim Tasarımı ) dallarının verilip verilmediği tespit edilmeye çalışılmıştır. Araştırma; İstanbul’da Giysi Tasarımı eğitimi veren Anadolu Meslek, Kız Meslek ve Çok Programlı Liselerinden oluşan toplam 13 okulda yürütülmüştür. Bu okullarda ki Tekstil Konfeksiyon Alanı; Kadın, Erkek, Çocuk Giysi Tasarımı dalını uygulayan öğretmenlerin, yöneticilerin görüş ve değerlendirmelerini ortaya koymak, öğrenci çalışmalarını, okul fiziksel ve sektörel imkanlarını araştırmak amacı ile anket ve görüşme formu hazırlanmıştır. Ayrıca değerlendirmeye ilişkin yazılı dokümanlar (zümre toplantıları), öğrenci çalışmaları, öğrenci kayıtları ve eğitim raporları incelenmiştir. Ayrıca Türkiye genelinde farklı bölgelerden seçilen Anadolu Meslek ve Meslek Liseleri, Anadolu Kız Meslek ve Kız Meslek Liselerinden 10 farklı okulun bölümleri, öğretmen - öğrenci sayıları, proje çalışmaları, Tekstil Konfeksiyon Alanı, Giysi Tasarımı Eğitimi, atölye donanımı ve mezunların durumları araştırılmıştır. Araştırma kapsamında ki tüm okullarda Giysi Tasarımı yapılan ulusal ve uluslar arası projelerde araştırılıp; program-proje kaynaşmasında anlamlı bir ilişki olup olmadığı saptanmaya çalışılmıştır. Teze başlandığında tüm okullar da METGE( Mesleki Teknik Eğitimi Geliştirme) Projesi kapsamında Tekstil Konfeksiyon Alan uygulanmaktaydı. 2006-2007 Eğitim Öğretim yılında MEGEP ( Mesleki Eğitimi Güçlendirme ) Projesi kapsamında Giyim Üretim Teknolojisi kademeli olarak uygulanmaya başlanmıştır. Bu yeni programla dalların adı Kadın Giysi Tasarımı- Kadın Giyim Modelistliği, Erkek Giysi Tasarımı- Erkek Giyim Modelistliği, Çocuk Giysi Tasarımı- Çocuk Giyim Modelistliği olarak değiştirilmiş olup Giysi Tasarımı adı kaldırılmıştır. Araştırmayı hazırlama sürecinde bu program değişikliği; programlar arası geçiş dönemini gözlemleme fırsatını vermiş ve yeni program oluşumu hakkında bilgilenmemizi sağlamıştır.

In this thesis ; the Turkish Educational System,the historical development, the organizational structure and the duties of the Ministry of Education along with Vocational- Technical Secondary Education Institutions ,which affiliated with formal and non-formal education, are examined. With this examination it is seen that “Costume Design” education is taught at schools controlled by General Directorate of Technical Education for Girls under the “Textile Garment Area” program. Descriptions, aims, contents, curriculum, teaching periods, materials (Modules) of “Textile Garment Area” program and Costume Design education which taught under the “Textile Apparel Area” program are examined. The schools that have Textile Garment departments were listed to determine whether or not they have Costume Design” (Woman, Man, Child and Underwear Costume Design) branch. The study was carried out in 13 schools consisting of Anatolian Vocational, Girls’ Vocational and Multi-Program High Schools that have Costume Design programs in İstanbul. Poll and discussion forms were prepared to investigate student work, physical and sectoral opportunities of the school and display opinions and evaluations of teachers and directors who execute Textile Garment Area; Woman, Man, Child Costume Design branch in those schools . The documents (class meetings), student works, student records and education reports were also analyzed Furthermore from the different regions throughout Turkey, 10 schools containing Anatolian Vocational, Vocational, Anatolian Girls’ Vocational and Girls’ Vocational High Schools were selected. The departments, the number of teachers-students, project works, Textile Garment Area, Costume Design Education, workshop facilities, status of the graduates of the selected schools were studied. Completed national and international projects in relation with Costume Design program in all schools within the scope of the research were examined .The results were analyzed to find out a meaningful relation between program-project coalescence Textile Garment Area Program had been executed within the METGE (Vocational Technical Education Development) Project in all schools by the time thesis work was started. With the beginning of school year 2006-2007, Clothing Production Technology program has started gradually under MEGEP (Fortification of Vocational Education) Project. With the new program the branch names has been changed from Woman Costume Design, Man Costume Design, Child Costume Design to Woman Costume Designer, Man Costume Designer and Child Costume Designer. Costume Design name had been removed. During the preparation of the research, this program modification has given us the opportunity to observe the inter-program transtion period and get acquainted with the formation of the new program.
Keywords: Ortaöğretim_Giysi Tasarımı